Identification and control of crane swing reduction using artificial neural network - Đặng Viết Phương Nam,; Ngô Văn Thuyên , (Journal of Technical Education Science, 2012)
This paper presents crane swing reduction control method by identifying the capacity of an artificial neural network. The mathematical model of crane is built from physical laws using Lagrange method. This model is used to find responses of the system, and to simulate identification and control process. A recurrent artificial neural network is used to identify and control the crane to reduce its load swing by supervised learning. Identification and control are done in simulation and implemented in a real system. Results of simulation and application in the real show that an artificial neural network can very well identify and control the crane swing reduction